Compact Millimeter-Wave Single- and Dual-Band On-Chip Bandpass Filters Using GaAs Technology - Yongzheng Li; Xiaoyu Weng; Kai-Da Xu (IEEE Journal of the Electron Devices Society)
In this paper, two compact on-chip bandpass filters (BPFs) at millimeter-wave frequencies, i.e., single-band BPF and dual-band BPF, are proposed in gallium arsenide (GaAs) technology. To understand the working mechanism of the single-band BPF, a transmission line (TL) equivalent circuit model is presented and analyzed to estimate the position of the transmission zeros (TZs). Based on the single-band BPF structure, two additional metallic strips on M1 layer are placed beneath the pair of meander strips to construct a dual-band BPF. Consequently, a dual-band frequency response can be realized by introducing two TZs within the passband. For demonstration, two prototypes of the BPF are fabricated and tested to validate the proposed idea, whose simulated and measured results are in good agreement. Both of the single- and dual-band BPFs have the same chip size of only 0.29 mm $× 0$ .23 mm, excluding the feeding.